Identifying Aid Effectiveness Challenges in Fragile and Conflict-Affected States - Ishihara, Yoichiro (World Bank, Washington, DC, 2012)
Fragile and conflict-affected states face daunting challenges for development. Aid has a greater importance on development in these states than in others, and therefore aid effectiveness management and delivery of aid bears serious consideration. Despite its significance, aid effectiveness is appreciably lower in fragile and conflict-affected states than in others. What are the key aid effectiveness challenges in these states and how can these issues be better addressed? As important initial steps, this paper aims to identify (i) aid effectiveness challenges facing fragile and conflict-affected states and (ii) good aid effectiveness examples using the results of the Survey on Monitoring the Paris Declaration on aid effectiveness, which was designed as a mechanism to support global and country level accountability. Both fragile and conflict-affected states (recipients) and development partners (providers) are mutually accountable for aid effectiveness; therefore, this paper focuses on both sides. While the analysis confirms the significantly lower aid effectiveness performance in fragile and conflict-affected states -- especially on aid on budget, aid predictability, and use of country systems -- good performance examples in several of these states are identified. The aid effectiveness performance of development partners in fragile and conflict-affected states differs significantly across different groups. Multilateral development banks and other multilateral organizations perform better on average than bilateral organizations and vertical funds. Disaggregation of development partner performance at the institutional level and the partner country level enables the analysis successfully to identify good performance examples. In using the results of this paper to improve aid effectiveness, key additional steps should include (i) considering whether the identified challenges are essential; (ii) analyzing the factors/reasons behind good performance examples; and (iii) discussing whether good performance examples can provide lessons that can be adapted and applied.